Resistividade elétrica de concretos de cimento Portland branco e elevados teores de escória de alto forno - Lübeck, André (2008)
The electrical resistivity is an important concrete property that allows evaluating the access facility of aggressive agents before the corrosion process begins and estimates the velocity of the same process after it begun. The electrical resistivity and the oxygen availability are the characteristics that control the corrosion velocity. This work aimed to evaluate the performance of white Portland cement concretes with high blast furnace slag content and chemical activation on the electrical resistivity. Other properties were measured, as axial compressive strength, porosity and specific electrical conductivity of pore solution. Four mixtures were tested, a reference one, only with white Portland cement as binder, a second one, with 50% of blast furnace slag in substitution of cement, other with 70% slag content, and the last one, with 50% of slag and alkaline activation, 4% of Na2SO4. The water/binder ratios were fixed at 0,30, 0,42 and 0,55 for all samples. The electrical resistivity was measured using the four electrode method (Wenner method). The sample age, water/binder ratio and the slag content have an expressive effect over the electrical resistivity, especially because it results in changes of the pore structure. The electrical resistivity grows as the amount of slag increases. The increase of slag amount also results in smaller specific electrical conductivity of pore solution and pore structure refinement. On the other hand, the axial compressive strength decreases as the slag amount increases. The biggest resistivity results were obtained for the mixture with 70% of slag. This mixture showed the best cost/benefit ratio as compressive strength were fixed at 35 and 55 MPa, at 28 days, and 60 MPa, at 91 days.